Alliance and CCAFS research advise on projected $130M-205M in investments of African Improved Foods in Ethiopia and Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Alliance and CCAFS researchers have produced studies advising African Improved Foods (AIF) on opportunities for projected $130M-205M in investment in prioritized value chains in Ethiopia and Kenya, sourcing from an estimated 270k farmers. Based in Rwanda as a public-private partnership involving DSM, Government of Rwanda, and others, AIF is using this research to guide its entrance into the Ethiopian and Kenyan markets, by helping to identify climate-smart and nutrition-sensitive investments in specific value chains.